High signal to noise absorption imaging of alkali atoms at moderate magnetic fields - Hans, Maurus; Schmutte, Finn; Viermann, Celia; Liebster, Nikolas; Sparn, Marius; Oberthaler, Markus K.; Strobel, Helmut (Review of scientific instruments, 2021)
We present an improved scheme for absorption imaging of alkali atoms at moderate magnetic fields, where the excited state is well in the Paschen-Back regime, but the ground state hyperfine manifold is not. It utilizes four atomic levels to obtain an approximately closed optical cycle. With the resulting absorption of the corresponding two laser frequencies, we extract the atomic column density of a 39K Bose-Einstein condensate. The scheme can be readily applied to all other alkali-like species.
Gesehen am 14.04.2021